OPTIMALISASI LEMBAGA PENDIDIKAN ISLAM MELALUI MANAJEMEN STRATEGIK ANALISIS SWOT - Rahmi Fentina Sari (Universitas Islam Negeri Sumatera Utara Medan, 2017)
In the 21st century Islamic school as an evolution from the school is still reaping the impact and challenges that need to always get a comprehensive treatment. The existence of islamic educational institutions consisting boarding school, Madrasah and other Islamic schools are determined by the management. Management is one importants component in any organization or institution of islamic education that expected to steer the spirit of educational activities to be effective and efficient, so that to achieve the goals set earlier. Principle analysis of SWOT and POAC as a method of organization development is the spirit of an organization so that the principle of absolute terms developed within the organization (Islamic Educational Institutions).